PENERAPAN TACIT KNOWLEDGE DAN EXPLICIT KNOWLEDGE: PENGARUHNYA TERHADAP KINERJA KARYAWAN DAN KEBIJAKAN KOMPENSASI (Studi pada Karyawan Hotel Zam Zam Kota Batu) - M. Taufiq Setiawan (Jurnal MD, 2017)
The aim of this research is to analyze and explain the influence of tacit knowledge on the employee performance, the influence of explicit knowledge on the employee performance, the influence of tacit knowledge on the compensation policy, the influence of explicit knowledge on the compensation policy, and the influence of employee performance on the compensation policy. The research is conducted in Hotel Zam Zam, located in Batu Tourism City, East Java. The population of the research is 50 employees of Hotel Zam Zam. This research uses saturated sampling or population sampling, with the whole population of 50 people as the sample. Questionnaires were used to obtain the data. The research results show that: First, tacit knowledge significantly influences employee performance; second, explicit knowledge significantly influences employee performance; third, tacit knowledge significantly influences compensation policy; fourth, explicit knowledge significantly influences compensation policy; and the last, employee performance significantly influences compensation policy.